Konsumsi dan Strategi Pemenuhan Kebutuhan Beras pada 2015 di Jawa Barat - Iskandar Ishaq (Puslitbang Tanaman Pangan, 2011)
Rice is an important food crop in West Java. It provides employment to 2.5 million farm households and another 2.7 million farm laborers. Presently, production of rice is sufficient to feed the population in the province of 42.2 million people and even there is one million ton of rice surplus. In 2015 West Java province will have 40.6 million inhabitants, requiring about 6.8 million ton of rice grain, or equivalent to 10.8 million ton of dry paddy. To meet the demand, it requires 1.93 million ha of rice to be planted annually, which is larger compare with the area of the present farm lands. To overcome this shortage, four strategies are suggested, namely: (1) increases the productivity of wet land and upland rice, (2) increases the planting intensity on irrigated and rainfed farm lands, (3) expanding upland rice cultivation on the newly planted estate crops and forest tree lands, (4) improves post harvest handling to reduce losses. Harmonious coordination among all stake holders in various government levels is required in order to implement such strategy. A good working relation between research institutes and agriculture extension is also needed to promote the adoption of appropriate adaptive technologies.